2012
DOI: 10.1108/17542731211191212
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐design in total environmental quality management

Abstract: Purpose -The purpose of this paper is to propose a methodology that may aid in assessing ecological quality multi-trait screening through the use of simple and robust tools while exerting minimal effort in conducting trials and interpreting results. Design/methodology/approach -Response data for two popular site-monitoring environmental indicators, chemical oxygen demand (COD) and biochemical oxygen demand (BOD), are arranged by implementing an 8-run saturated orthogonal array proposed by Taguchi. Unreplicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The studies also showed that QM improves environmental, social, and financial outcomes (Besseris, 2012;Cherrafi et al, 2016;Siva et al, 2016;Zhu et al, 2013). For example, Ruben et al (2018) proposed a framework that integrates Lean Six Sigma (LSS) with the environmental aspects associated with the manufacturing process.…”
Section: Qm and Sustainabilitymentioning
confidence: 99%
“…The studies also showed that QM improves environmental, social, and financial outcomes (Besseris, 2012;Cherrafi et al, 2016;Siva et al, 2016;Zhu et al, 2013). For example, Ruben et al (2018) proposed a framework that integrates Lean Six Sigma (LSS) with the environmental aspects associated with the manufacturing process.…”
Section: Qm and Sustainabilitymentioning
confidence: 99%
“…It was important to be ordinary people, recruited among the students at the EDIM Department (Ergonomie Design et Ingénierie Mécanique) of the UTBM (Université de Technologie Belfort Montbéliard). This type of recruitment guaranteed the homogeneity of the sample in terms of age, socio-cultural background, education, and sensory design knowledge [1,5,[22][23][24][25].…”
Section: The Subjectsmentioning
confidence: 99%
“…Hypothesis 4: Organizational Excellence mediates the relationship between TQM practices and sustainable performance Environmental regulation and policy as a moderator between total quality management (TQM) practices and sustainable performance (SP) Undoubtedly, both TQM and ERP have attracted the attention of people both in business and academic environment (Ahmad and Schroeder 2002;Besseris 2012). Such popularity can be referred back to the unprecedented high number of published articles in both fields in an attempt of the scholar in the fields to validate its theories and concepts.…”
Section: Organizational Excellence and Sustainable Performancementioning
confidence: 99%